Effectiveness of Group Counseling Using the Actualizing Human Strengths Technique to Enhance Student Empathy - Uswatun Hasanah; Saiful Akhyar Lubis (Journal of General Education and Humanities, 2025)
This study aims to determine the effectiveness of group counseling services using the Actualizing Human Strengths technique in fostering student empathy. The approach used is a quantitative method with a one-group pretest-posttest Design. The research subjects consisted of six 7th-grade students from class VII-J at MTsN 2 Medan who were identified as having low levels of empathy based on the pretest results. Data were collected using an empathy scale questionnaire modified from the Interpersonal Reactivity Index (IRI) and analyzed using normality tests, homogeneity tests, and the Paired Sample T-Test. The results revealed a significant increase in empathy scores after the intervention, with a significance value of 0.000 (p < 0.05). These findings indicate that group counseling services employing the Actualizing Human Strengths technique effectively enhance empathy among students at MTsN 2 Medan.